Penerapan Pendekatan Matematika Realistik Pada Materi Perkalian Untuk Meningkatkan Hasil Belajar Peserta Didik Di Kelas III A SDN 5 Banda Aceh - Fatra, Juanda; Fauzi, Fauzi; Nurhaidah, Nurhaidah (Universitas Syiah Kuala, 2022)
The purpose of this study is to describe the activities of teachers and students and to determine student learning outcomes on multiplication material through a realistic mathematical approach. Qualitative approach is the approach in this research and classroom action research (CAR) is the type of research. 28 students in class III A-SDN 5 Banda Aceh are the research subjects. This research was carried out in three cycles and each cycle went through four stages, namely: planning, implementation, observation and reflection. Observation sheets and test sheets are data collection techniques. Descriptive statistics is an analytical technique in this study. According to the results of the analysis that has been done through the activities of teachers, students, and student learning outcomes are (a). The average result of teacher activity in the first cycle is 3.00, for the second cycle is 3.61 and for the third cycle is 4.53. (b). The average results of student activities for the first cycle is 2.50, for the second cycle is 3.37 and for the third cycle is 4.50. (c). Student learning outcomes for the first cycle obtained an average value of 68 on the percentage of classical completeness is 46%, for the second cycle the average value of 73 on the percentage of classical completeness is 71.42%, and for the third cycle the average value is 86 on the percentage of classical completeness is 85.71%. From the data analysis of each cycle, it can be concluded that the application of a realistic mathematical approach can develop teacher and student activities and can improve student learning outcomes in multiplication material in class III A SDN 5 Banda Aceh.